WIRELESS PRESSURE GAUGE SYSTEM FOR VEHICLE - Maheshkumar G. Pawar; Tousif A. Tamboli; Harshila S. Kisave; Ashish V. Amrute (International Journal of Innovations in Engineering Research and Technology, 2021)
Today safety of human life major concerns. Nowadays up to 60-65% accidents are occurs due to transport of vehicle. These are occurring especially the low or high tire pressure and temperature (i.e. it increases the temperature of tire by friction). So tire burst is avoiding during a superhighway that time the instrument are used to prevent accident are “Wireless pressure gauge system for vehicles with air bag system”. In a wireless pressure gauge system for vehicle are used to measure the pressure and temperature of each tire and fill the air automatically and also it indicate the digital display. Also this project deals with the air bag system, at worst condition driver unable to stop the vehicle. Finally these kinds of instrument are used for a society and improve the need of practical application in more amounts.